A Revision of Chusquea sect. Serpentes (Bambuseae, Bambusoideae, Poaceae) Including Two New Species from South America - McMurchie, Elizabeth K.; Peterson, Bryan J.; Leandro, Thales D. [UNESP]; Londoño, Ximena; Clark, Lynn G. (American Society of Plant Taxonomists, 2022)
The Neotropical woody bamboo genus Chusquea consists of 193 currently described species ranging from central Mexico and the Caribbean to Chile and Argentina, primarily in montane habitats. The six previously described species of Chusquea subg. Chusquea sect. Serpentes are scandent in habit, with infravaginal branching, few subsidiary buds per complement, and foliage leaves that tend to be relatively large compared to those of other members of Chusquea s.s. A review of available material of Chusquea sect. Serpentes, found throughout montane forests from Mexico south to the central Andes in Peru, revealed at least two undescribed species. One of the new species, Chusquea recurvata, is native to Venezuelan montane forests and is distinguished from Chusquea serpens by having circular central buds, asymmetrical, acute inner foliage leaf ligules, and 6-12 foliage leaves per complement. The other new species, Chusquea acutigluma, has been found only in and around the Risaralda gorge in Colombia, and differs from all other known South American species of Chusquea sect. Serpentes by its broadly open paniculate synflorescences. This paper includes (re-)descriptions of all known species of Chusquea sect. Serpentes, along with detailed photographs of the two newly described species, and a vegetative morphological key to the eight species belonging to the section. The morphology and foliage leaf micromorphology and anatomy of the two newly described species are compared to C. serpens, to which they show the greatest macromorphological similarity.
Keywords: Andes; Chusqueinae; leaf anatomy; leaf micromorphology; montane forests; Neotropical woody bamboos